Pengaruh Pola Asuh Orang Tua Membangun Kepercayaan Diri Anak - Paiman Nahrodi; Hasbullah Hasbullah; Hanafi Hanafi (Pusat Kajian Islam dan Kemasyarakatan (PKIK), UIN Sultan Maulana Hasanuddin Banten, 2022)
This writing was used qualitative library research. The writer tries to describe the activities, program, curriculum and the children of development steps. The goals of writing, was to understand the deep about the patterns to take care of building the children's confidences, Family as the first institution in their live will be educating them. The family as the place for learning and teaching process themselves as the social animal. Generally, in the family, the children will make the close relation each other. The family will give the reformed of attitude, behavior. morality and education. The pattern to take care of children as the all methods of parents who decided for their children, as the parts of the important and base to prepare their polite and a good children character. The reform of self-confidence, discipline attitude, fairness value and achievement motivation and spirituality aspect to our children as the base of children's character to achieve. The psychological and spirituality aspect for our children done in order to the parents will be produced by the pattern to take care of authoritative who support a significant children's achievement.